Strategic Management Capabilities and Sustainable Competitive Advantage in Nepal’s Hospitality Sector - Shah, Bijaya Bikram (Nepalese Journal of Management and Technology, 2025)
This study investigates the role of strategic management capabilities in achieving sustained competitive advantage in Nepal’s emerging hospitality industry, which is undergoing a shift from traditional service delivery toward experience-driven competition. A quantitative research design was adopted using primary data collected from 477 respondents representing star-rated hotels, boutique resorts, and homestays across major tourist destinations, including Kathmandu, Pokhara, and Chitwan. Data were cleaned and processed using Python, and Structural Equation Modelling (SEM) was employed to examine the relationships among adaptive resource allocation, technological integration, dynamic leadership, and sustained competitive advantage. The findings indicate that while tangible resources contribute to short-term competitive parity, long-term competitiveness is predominantly driven by intangible strategic capabilities. Specifically, the strategic alignment of human capital, service innovation, and leadership adaptability demonstrates a significant positive influence on sustained competitive advantage. These results highlight the critical importance of dynamic capabilities in responding to changing market conditions within emerging tourism economies. The study provides practical insights for hospitality managers to focus on leadership development, strategic technology integration, and effective human capital utilization to strengthen long-term competitive positioning.